Daurah Al-Mâ’ ‘Inda Zaghloul An-Najjâr - Ali Mahfuz Munawar; Ike Nuraini (Universitas Darussalam Gontor, 2018)
The Hydrological Cycle is one of the miracles in the Qur'an. Hydrology is a study about the water cycle in the earth. In the fourteenth century, there was a serious conflict among the scientist 's thoughts about the begining of water on the surface of the earth. The emergence of this conflict, because the scholars assume that Allah SWT has taken out every water in the earth from it, and its cycle between the earth and the sky. Then a French scientist named Bernard Palissy argued that rivers and springs would not be the primary source of water without rain. And one of mufaseer who stating this opinion is Zaghloul An-Najjar. He is the chief of general assembly of al-I'jaz committee in Egypt. He is the expert in the field of al-I'jaz al-Ilmy in the Qur'an and Hadith, which is famous for his discussion of the Qur'an and the Hadith in terms of his scientific i'jaz. This paper seeks to examine the water cycle in Zaghloul an-Najjar perspective by integrating the Qur'an and science.